LAPAROSCOPIC CHOLECYSTECTOMY IN ELDERLY PATIENTS PRESENTING WITH ACUTE CHOLECYSTITIS - Muhammad Umar Rashid; Javaid Iqbal (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives: The aim of this study was to determine the frequency of wound infection and length of postoperative hospital stay for laparoscopic cholecystectomy (LC) in elderly patients presenting with acute cholecystitis. Study design: Case series. Settings and duration of study: This study was conducted in surgical departments, Allied and DHQ Hospitals Faisalabad from Aug, 2009 to Jan, 2010. Patients and Methods: The study included 85 patients over 55 years of age with acute cholecystitis undergoing laparoscopic cholecystectomy. All the patients in the study were subjected to LC during same admission. Preoperative parameters of age and sex were analyzed on the basis of postoperative wound infection and length of postoperative hospital stay. Statistical analysis was done using SPSS version 10. Results: Mean age was 62.7 years with female to male ratio 3.47:1. History of previous abdominal surgery was present in 18 patients. A total of 55 patients were operated within 48 hours and 30 patients after 48 hours from onset of symptoms. Wound infection was seen in 6 patients (4 males and 2 females). Postoperative hospital stay was <2 days in 45 patients and >2 days in 40 patients. Age >65 years, male gender, positive history of previous abdominal surgery, leukocytosis and timing of surgery from onset of symptoms (>48 hours) were found to be the main factors for high morbidity. Conclusion: Laparoscopic cholecystectomy can be performed safely in elderly patients with acute cholecystitis. Although there are some factors associated with high risk of wound infection and longer hospital stay. But with good selection of cases and surgical skills, overall morbidity can be reduced.